Implementasi Pendidikan Karakter Di Sd Negeri Soropadan No. 108 Surakarta Dan Sd Muhammadiyah 16 Karangasem Surakarta - Sulistyaningsih, Endang S, Dr. Bambang Sumarjoko, M. Pd, Dr. Ahmad Muhibbin (2017)
The objectives of the research are to know and describe: 1) the planning and implementation of character education; 2) the output of the character education implementation; and 3) the supporting and inhibiting factors of the character education implementation at SD Negeri Soropadan No. 108 Surakarta and SD Muhammadiyah 16 Karangasem Surakarta. The type of the research is a qualitative research. The design of the researh is a case study. The research was undertaken at SD Negeri Soropadan No. 108 Surakarta and SD Muhammadiyah 16 Karangasem Surakarta. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The research concludes that: 1) the character education planning were done by identifying the characters values developed from schools' visions and missions. The implementation were done in the form of extra curriculer and intracurriculer activities; 2) the output of the character education implementation were the developed and understandable of the characters' values as a result of characters' values internalization; and 3) the supporting factors in the character education implementation were the high committment of the schools' stakeholders to actualize the schools' visions, namely creating good conduct human being. The inhibiting factors of the character education implementation mostly come from psychological aspects of the actors